Spectroscopic studies of electron transfer reactions at the photoactive electrode of dye-sensitized solar cells - Antila, Liisa (2013)
Harnessing solar energy is a key issue in solving the global energy challenge. The Sun's radiant energy can be converted into electricity by photovoltaics. One of the most promising, emerging PV technologies is the dye-sensitized solar cell. In order to develop this technology, understanding the dynamics of charge separation and electron transfer reactions in the cell is of fundamental importance. In this thesis, rates of electron transfer in dye-sensitized titanium dioxide films and complete solar cells were investigated by means of transient absorption and transient emission spectroscopies, as well as with electrochemical impedance spectroscopy. The effect of altering electron transfer rates on the performance of the cells was monitored by recording the current-voltage response of the cells under simulated sunlight. Electron transfer from two ruthenium dyes to titanium dioxide film (electron injection) in neat solvent and in the presence of an iodide/triiodide electrolyte was studied by following the ultrafast temporal evolutions of the absorptions of oxidized dye and of injected electrons. Electron injection was found to be almost two orders of magnitude slower in the presence of the complete electrolyte compared to injection in neat solvent. Comparison of the transient absorption signals of the oxidized dye and injected electrons of the sensitized TiO2 films in contact with the I-/I3- electrolyte revealed the picosecond time scale of dye regeneration for the first time, twenty years after the invention of the cell. This observation also paves the way for understanding the detailed molecular mechanisms of the function of the electrolyte redox couple in the cell. Metal oxide barrier layers deposited on the nanocrystalline TiO2 film were studied as a means to improve cell performance. The desired effect of the barrier layer is to slow down recombination reactions while maintaining good electron injection efficiency. Barrier layers were prepared with atomic layer deposition for better controllability of layer thickness and morphology. Aluminum oxide was found to slow down injection more than recombination, which led to deterioration of cell performance. Hafnium oxide barriers up to four atomic layer cycles retarded injection much less than the corresponding aluminum oxide layers, and in practice, retained cell performance. According to this result, increasing hafnium oxide layer thickness and improving its penetration into TiO2 film would provide a means to improve cell performance. Surprisingly, a relatively thick (about 1nm) tantalum oxide coating resulted in enhancement of the injection efficiency and led to about a 10% increase in the current output of the cell. This finding was significant as no barrier layer on TiO2 so far has been reported to have shown an increase in injection efficiency. More interestingly, improved cell performance was obtained for the TiO2 film with only the top quarter of the film covered with tantalum oxide.